Konsep dan Implementasi Corporate Social Responsibility (CSR) Pada Perbankan Syariah - Muhammad Imam Purwadi (Jatiswara, 2016)
Corporate Social Responsibility (CSR), has become an interesting issue both in social and development sectors for many parties. It makes Corporate Social Responsibility (CSR) is increasingly debated as the issuance of various regulations of the Republic of Indonesia government. CSR is an approach in which companies integrate social concerns in their business operations and in their interaction with stakeholders based on the principle of voluntarism and partnership. In Indonesia, the obligation to implement CSR not only imposed on the State Owned Enterprises (BUMN), but also on the companies to undertake the community development, either in the social, educational, economic, environmental and health aspects. Through UU No. 40 Year 2007 concerning Limited Liability Companies and UU No. 25 Year 2007 on Investment, any company or investor is required to perform an implementation of corporate responsibility efforts that have been budgeted and accounted as expenses of the Company. Islamic Banking as a company that is subject to the UU No. 21 Year 2008 concerning Islamic Banking and UU No. 40 Year 2007 regarding Limited Liability Company, is the company that runs the programs and policies of the State in the economy and social welfare through the efforts of Islamic banks that is subject to the investment law, as stipulated in Law No. 25, Year 2007, concerning Investment. In UU No. 21 Year 2008, concerning Islamic Banking, stated that Islamic banking in its function aims at supporting the implementation of national development in order to enhance the justice, solidarity and equitable welfare. As one of the objectives of the implementation, Islamic banking can perform its social function in the form of Baitul Mal (treasury), which receives funds from zakat, donation, charity, or other social funds and distribute them to the community. In its social mission, Islamic banking has financing product namely qardhul al-hasan. This product can be categorized as a form of social responsibility (CSR) of Islamic banks which cannot be obtained from conventional banks. Thus, al-qardhul hasan as a social function of Islamic banks is very strategic in the effort to realize the public welfare through Islamic economy instruments.